Faktor Risiko Yang Berhubungan Dengan Kejadian Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Purbaratu Kota Tasikmalaya - Nuryantini, Puput; Setiyono, Andik; Annashr, Nissa Noor (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Currently, the prevalence of diabetes mellitus (DM) is steadily increasing globally. In 2022, the highest number of diabetes patients in the city of Tasikmalaya were found in the working area of Puskesmas Purbaratu The purpose of this study is to analyze risk factors associated with the occurrence of type 2 diabetes mellitus in the Puskesmas Purbaratu working area in Tasikmalaya in 2023, using a case-control design. The case population consists of type 2 DM patients recorded during the period of January-June 2023 at the Purbaratu Community Health Center The control population consists of respondents who are not type 2 DM patients in the Purbaratu Community Health Center's working area. For the case group, a total of 86 individuals were sampled For the control group, samples were taken using purposive sampling technique, with a 1:1 ratio, resulting in a total of 86 control samples. Data was collected through questionnaire interviews. Univariate and bivariate analysis with chisquare test was performed. The results showed that there was no association between type 2 DM and family history of DM (p-value = 0.000 with OR= 2.423) and physical activity (p-value = 0.000 with OR= 2.655). Dietary risk factors (p-value = 0.436) had no association. Based on the results of the study, to minimize the incidence of type 2 DM, it is recommended to apply a healthy lifestyle, namely a nutritious diet, regular health checks and regular exercise.Keywords: Diabetes mellitus, risk factors